Results of longitudinal Nutri-D study: factors influencing winter and summer vitamin D status in a Caucasian population - Hribar, Maša; Pravst, Igor; Pogačnik, Tina; Žmitek, Katja (Frontiers in Nutrition, 2023)
Inadequate vitamin D status is a worldwide public health issue. In humans, vitamin D status is affected by diet, and even more by exposure to ultraviolet B (UVB) light and consequential endogenous synthesis. Various personal and environmental factors influence endogenous synthesis. Factors affecting vitamin D status were investigated in a prospective longitudinal cohort study with a summer and winter observation period. The final sample included 292 adults, of those 111 (38 %) males and 181 (62 %) females, with a mean age of 38.2 (±11.8) years from Slovenia who were not supplementing vitamin D. Serum 25-hydroxyvitamin D (25(OH)D) concentrations were measured in both periods; vitamin D intake, self-reported body mass index (BMI), and protective behaviours against sun were also recorded. Other measured parameters included measurements of constitutive skin colour using the objective individual typology angle (ITA), and difference in the melanin index (ΔMI) for assessment of objective sun exposure. In winter a high prevalence (63.4 %) of insufficient vitamin D status (< 50 nmol/l) was observed with higher odds ratios (OR) for insufficiency in those with a higher BMI and light ITA. During summer, insufficiency prevalence was low (5.5 %), but half of the participants (50.0 %) had suboptimal 25(OH)D concentration (< 75 nmol/L). In summer OR for suboptimal status were higher in those with obesity, lower ΔMI, light ITA, low vitamin D intake, and protective clothing behaviours. Using a series of measures, we showed that vitamin D status is hugely affected by several personal factors such as BMI, ITA, vitamin D intake, ΔMI, and protective behaviour against the sun. This conclusion questions the usefulness of generalised population-level recommendations since personal factors are a major predictor of vitamin D status.